The language of negotiation a multimodal discourse analysis of transactions in Philippine livestock auction markets - Salvador, Kahrein A. Yapo, Jerry R. (UP Los Baños Journal, 2014)
This exploratory study examined how business negotiations are performed in Philippine livestock auction markets. It identified underlying factors, such as culture, discourse and power, which influence the outcome of such transactions. Using a qualitative approach, the research is hinged on Norman Fairclough's three-dimensional model of discourse. Examined were transactions in the two largest livestock auction markets in the country - Urdaneta, Pangasinan and Padre Garcia, Batangas - with three discourse analysis method: ethnography of communication, conversation analysis and critical discourse analysis. Findings reveal that to the participants, negotiations in livestock auction markets, more than being a linguistic practice, are a communal experience. Central to how participants negotiate is their cultural setting. Livestock exchange appears to be a male-dominated profession. Participants mainly transacted to buy and/or sell livestock. Buyers normally started the transactions with either a verbal or non-verbal greeting, signifying an intention to participate....